Melatonin: Bone Metabolism in Oral Cavity - Fanny López-Martínez; Patricia N. Olivares Ponce; Miriam Guerra Rodríguez; Ricardo Martínez Pedraza (Hindawi Limited, 2012)
Throughout life, bone tissue undergoes a continuous process of resorption and formation. Melatonin, with its antioxidant properties and its ability to detoxify free radicals, as suggested by Conconi et al. (2000) may interfere in the osteoclast function and thereby inhibit bone resorption, as suggested by Schroeder et al. (1981). Inhibition of bone resorption may be enhanced by a reaction of indoleamine in osteoclastogenesis. That it has been observed melatonin, at pharmacological doses, decrease bone mass resorption by suppressing through down regulation of the RANK-L, as suggested by Penarrocha Diago et al. (2005) and Steflik et al. (1994). These data point an osteogenic effect towards that may be of melatonin of clinical importance, as it could be used as a therapeutic agent in situations in which would be advantageous bone formation, such as in the treatment of fractures or osteoporosis or their use as, a bioactive surface on implant as suggested by Lissoni et al. (1991).